Housekeeping Gene Selection Advisory: Glyceraldehyde-3-Phosphate Dehydrogenase (GAPDH) and β-Actin Are Targets of miR-644a - Kavleen Sikand; Jagjit Singh; Jey Sabith Ebron; Girish C. Shukla (2012)
Results of overexpression or downregulation of a microRNA (miRNA) on its target mRNA expression are often validated by reverse-transcription and quantitative PCR analysis using an appropriate housekeeping gene as an internal control. The possible direct or indirect effects of a miRNA on the expression of housekeeping genes are often overlooked. Among many housekeeping genes, expressions of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and β-actin have been used extensively for normalization of gene expression data. Here, we show that GAPDH and β-actin are direct targets of miR-644a. Our data demonstrate the unsuitability of GAPDH and β-actin as internal controls in miR-644a functional studies and emphasize the need to carefully consider the choice of a reference gene in miRNA experiments.